2006
DOI: 10.1523/jneurosci.3459-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Human Taste Thresholds Are Modulated by Serotonin and Noradrenaline

Abstract: Circumstances in which serotonin (5-HT) and noradrenaline (NA) are altered, such as in anxiety or depression, are associated with taste disturbances, indicating the importance of these transmitters in the determination of taste thresholds in health and disease. In this study, we show for the first time that human taste thresholds are plastic and are lowered by modulation of systemic monoamines. Measurement of taste function in healthy humans before and after a 5-HT reuptake inhibitor, NA reuptake inhibitor, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
157
3
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(174 citation statements)
references
References 58 publications
6
157
3
8
Order By: Relevance
“…Not only has a history of smoking been shown to reduce serotonin levels centrally (Benwell et al, 1990), but the acute administrations of Paroxetine, a specific serotonin reuptake inhibitor, in healthy individuals decreased sweet and bitter taste thresholds (Heath et al, 2006). Moreover, individuals with seasonal affective disorder (SAD), a disorder postulated to be due to a decreased central serotoninergic function (Rosenthal et al, 1987), had higher taste thresholds for sweet, bitter, and salty tastes during the winter, when they are depressed, but thresholds normalized during the summer, when the symptoms of depression disappeared (Arbisi et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Not only has a history of smoking been shown to reduce serotonin levels centrally (Benwell et al, 1990), but the acute administrations of Paroxetine, a specific serotonin reuptake inhibitor, in healthy individuals decreased sweet and bitter taste thresholds (Heath et al, 2006). Moreover, individuals with seasonal affective disorder (SAD), a disorder postulated to be due to a decreased central serotoninergic function (Rosenthal et al, 1987), had higher taste thresholds for sweet, bitter, and salty tastes during the winter, when they are depressed, but thresholds normalized during the summer, when the symptoms of depression disappeared (Arbisi et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence here suggests that indeed it can. So, for example, it has been shown that a person's mood can influence their ability to detect both olfactory (e.g., [90]) and gustatory stimuli ( [91][92][93]). In one representative study, Pollatos et al [90] presented their participants with pleasant, unpleasant, and neutral pictures from the International Affective Picture System (IAPS) database.…”
Section: Emotional Mediation Of Music's Influence On Tastementioning
confidence: 99%
“…Serotonin may modulate the threshold of sensory receptor cells in the taste bud or alter membrane properties in taste bud cells [138,139]. Indeed, a recent report from L. Donaldson's laboratory shows selective serotonin re-uptake inhibitors alter human taste thresholds for sweet and bitter via a peripheral mechanism [140]. Further investigation of the role of serotonin in taste buds is clearly needed.…”
Section: Information Flow In the Taste Budmentioning
confidence: 99%